2013
DOI: 10.1038/ncomms2535
|View full text |Cite
|
Sign up to set email alerts
|

COG complexes form spatial landmarks for distinct SNARE complexes

Abstract: Vesicular tethers and SNAREs are two key protein components of the intracellular membrane trafficking machinery. The COG (conserved oligomeric Golgi) complex has been implicated in the tethering of retrograde intra-Golgi vesicles. Here, using yeast two hybrid and co-immunoprecipitation approaches, we show that three COG subunits, namely COG4, 6, and 8, are capable of interacting with defined Golgi SNAREs, namely STX5, STX6, STX16, GS27, and SNAP29. Comparative analysis of COG8-STX16 and COG4-STX5 interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 41 publications
6
112
0
Order By: Relevance
“…This localization depends on the interaction of CnAβ1 with Cog8. Cog8 is an important player in the stabilization of the Cog and SNARE complexes required for the tethering and transport of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 vesicles to the Golgi, and in the regulation of the proper compartmentalization of Golgi proteins (Laufman et al, 2013;Willett et al, 2013). The localization at the Golgi apparatus is specific of CnAβ1 and suggests that this calcineurin isoform plays a different role from that of CnAβ2, which is distributed throughout the cytoplasm of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This localization depends on the interaction of CnAβ1 with Cog8. Cog8 is an important player in the stabilization of the Cog and SNARE complexes required for the tethering and transport of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 vesicles to the Golgi, and in the regulation of the proper compartmentalization of Golgi proteins (Laufman et al, 2013;Willett et al, 2013). The localization at the Golgi apparatus is specific of CnAβ1 and suggests that this calcineurin isoform plays a different role from that of CnAβ2, which is distributed throughout the cytoplasm of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to known CnA interacting proteins like CnB (Felkin et al, 2011), we identified the interaction between CnAβ1 and Cog8, a protein enriched mainly in the external Golgi as well as other intracellular membranes that is involved in the interaction with the Cog and SNARE complexes (Laufman et al, 2013;Willett et al, 2013;Willett et al, 2014) (Table S4). To validate this interaction, we transfected cells with GFP-CnAβ1 chimeras and carried out immunoprecipitation and colocalization experiments.…”
Section: Cog8 Drives the Localization Of Cnaβ1 To The Golgi Apparatusmentioning
confidence: 99%
“…Our previous work has shown that one of the functions of the COG complex is to serve as a landmark for two SNARE complexes, the cis-Golgi localized STX5 containing SNARE complex, and the trans-Golgi localized STX16 containing SNARE complex. 34 In order for the COG complex to organize these SNARE complexes, it is critical that they interact in the correct Golgi compartment. We believe that it is through the COGs multiple interaction profiles with membrane-bound partners (i.e., Rabs, SNAREs, coiled-coil tethers such as p115) that the compartment specificity of the COG complex is achieved.…”
Section: E27888-8 Cellular Logistics Volumementioning
confidence: 99%
“…Plasmids expressing FRB and FKBP12 fragments were obtained from Dr. Gambhir (Stanford University).To generate hCOG4-GFP-FRB and hCOG8-GFP-FRB constructs NdeI/KpnI fragments of siRNA-resistant hCOG4 and hCOG8 34 were sub-cloned into similarly digested c-Luc-FRB plasmid.…”
Section: Plasmid Preparation and Transfectionmentioning
confidence: 99%
“…Alterations in lobe A lead to accumulation of late glycosylation enzymes in COG complex vesicles, thereby preventing interaction with their substrate. Lobe B rather mediates vesicular sorting of trans-Golgi enzymes through functional interactions with the tethering and fusion machinery of trans-Golgi cisternae [67,68]. Accordingly, glycosyltransferases from early Golgi cisternae, such as the 1-2 GlcNAc-transferase MGAT1, are more affected by a defect in lobe A [66].…”
mentioning
confidence: 99%